Designing Prototype of Volume Detector for Medical Oxygen Cylinder Using NodeMCU ESP8266 - Mamad Muhamad Mansur; Rahmat Ismatullah Ibrahim; Ade Surya Budiman (Komunitas Dosen Indonesia, 2023)
The COVID-19 pandemic posed significant challenges to the healthcare sector, particularly due to the imbalance between patient numbers and available medical staff, resulting in difficulties during emergencies. One such challenge was the prompt replacement of oxygen cylinders. Leveraging Internet of Things (IoT) technology, we developed a prototype oxygen cylinder volume detector aimed at providing early notifications to healthcare professionals. This prototype incorporates the NodeMCU ESP8266, equipped with an Infrared (IR) Obstacle Sensor. The sensor communicates with a relay to activate an MP3 module, delivering audible alerts. Furthermore, the NodeMCU ESP8266 system integrates CTBot to send text notifications through the Telegram application to the nearest healthcare personnel. Visual alerts are also provided through red LED lights attached to the cylinders, indicating which oxygen cylinder is approaching depletion. Comprehensive testing validated the proper functionality of all system components. This innovative oxygen cylinder detector prototype is designed to streamline healthcare worker and nurse workflows by offering quicker access to accurate information regarding the status of medical oxygen cylinders. Not only does this enhance patient care efficiency, but it also ensuring the availability of oxygen is crucial for critical patients.